War and literature - Ashe, Laura; Patterson, Ian (Boydell & Brewer, 2014)
War was the first subject of literature; at times, war has been its only subject. In this volume, the contributors reflect on the uneasy yet symbiotic relations of war and writing, from medieval to modern literature. War writing emerges in multiple forms, celebratory and critical, awed and disgusted; the rhetoric of inexpressibility fights its own battle with the urgent necessity of representation, record and recognition. This is shown to be true even to the present day: whether mimetic or metaphorical, literature that concerns itself overtly or covertly with the real pressures of war continues to speak to issues of pressing significance. Particular topics addressed include writings of and about the Crusades and battles during the Hundred Years War; Shakespeare's "Casus Belly"; Auden's "Journal of an Airman"; and War and Peace. Contributors: Joanna Bellis, Catherine A.M. Clarke, Mary A. Favret, Rachel Galvin, James Purdon, Mark Rawlinson, Susanna A. Throop, Katie J. Walter, Carol Watts, Tom F. Wright, Andrew Zurcher